External, Integrated and Digital Personalization: How the Mobile Phone Became Unique - Reunanen, Markku; Lučenič, Adela Lujza; Noppari, Petra; Chen, Lu (Filmiverkko ry, 2026)
This article examines the development of mobile phone personalization from the mid-1990s to the early 2000s, focusing on three key categories: external, integrated and digital personalization. As mobile phones evolved from utilitarian devices to personal accessories, a wide range of stakeholders introduced options for consumers to personalize their devices. Phone cases, colorful covers, ringtones and operator logos gave birth to a complete industry supporting such customization. Drawing on two main sources, contemporary magazines and newspapers, and unforeseen material from the recently opened Nokia Design Archive, we use Madeleine Akrich’s concepts of script and projected user to analyze how these stakeholders shaped mobile phone personalization. More than surface-level decoration, such modifications became a key mechanism for technology adoption, individual distinction and cultural integration of mobile technology at the turn of the millennium, reflecting shifts in consumer identity, design practices and the emerging mobile media culture.